THE ROLE OF THE AUDIT COMMITTEE AND GENDER DIVERSITY IN THE QUALITY OF SUSTAINABILITY REPORT DISCLOSURES - Syahri, Syahri; Meutia, Inten; Sari Mustika Widyastuti (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2024)
This research aims to determine the role of the audit committee and gender diversity in Sustainability Reports. This research is a quantitative descriptive research that will use a causality approach in identifying the role of the audit committee and gender diversity on the quality of sustainability report disclosures. This research uses issuer data sourced from issuers' annual reports and sustainability reports from the NCCR website for the 2019-2021 period obtained from 231 companies. The analytical method used is multiple linear regression analysis. The research results show that the variables of audit committee size, frequency of audit committee meetings, proportion of financial expertise on the audit committee and gender diversity have a significant effect on the disclosure of Sustainability Reports. This shows that the role of gender diversity is very necessary in the quality of Sustainability Report disclosure.